If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6 + x + -5) = 3 + -1x Reorder the terms: 4(6 + -5 + x) = 3 + -1x Combine like terms: 6 + -5 = 1 4(1 + x) = 3 + -1x (1 * 4 + x * 4) = 3 + -1x (4 + 4x) = 3 + -1x Solving 4 + 4x = 3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4 + 4x + x = 3 + -1x + x Combine like terms: 4x + x = 5x 4 + 5x = 3 + -1x + x Combine like terms: -1x + x = 0 4 + 5x = 3 + 0 4 + 5x = 3 Add '-4' to each side of the equation. 4 + -4 + 5x = 3 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 3 + -4 5x = 3 + -4 Combine like terms: 3 + -4 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2
| 3(22-5)=2z+13 | | 4y+6y=90 | | 100xq=1.1387 | | -2+n=9 | | -6/5-(-3/2)= | | 2.8-10m=8.19 | | 3(a-5)=6a-(3a+15) | | 2v+5v-8=18 | | 3xy+6=p | | 4(6+x)-5=3-x | | 4(2-1)=-8(0.5-y) | | (8x+8)(4x^2+3x+5)= | | c^30+275=1225 | | =-12-8x-3/4 | | X^4-x^3-29x^2-x-30=0 | | 7t-4t+3-1=29 | | 4z+15=11 | | 5y-y+1=13 | | [2x+5]-5=-2 | | 10y+8=12x-18 | | 6(5-8v)+12=54 | | 2x+3+9=56 | | -7=10-x | | 500=45*c+35(12-c) | | -4+(-3)= | | 500=45*c+35(12+c) | | (8w+9)(-3)= | | 5k+(k+15)-3(k+2)=0 | | 5.7v-44.2=-8.3v | | 2x+15+27-4x= | | x=15-37 | | -.25y+3x=-2 |